(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
تسعى هذه الدراسة إلى التعرف إلى العوامل الاجتماعية والثقافية المسببة لسلوك العنف لدى طلبة المدارس, وشمل مجتمع الدراسة على تلاميذ مرحلة التعليم الأساسي الحلقة الثانية (الصف السابع, الثامن, التاسع الإعدادي) في المدارس الحكومية لمدينة اللاذقية في الجمهورية العربية السورية. وقد توصلت الدراسة إلى وجود علاقة ارتباطية بين أساليب العقاب التي يستخدمها الآباء مع التلاميذ واكتسابهم لسلوك العنف, ووجود علاقة ارتباطية بين الحرمان الاجتماعي في الأسرة وبين ظهور سلوك العنف لدى التلاميذ, وكشفت نتائج الدراسة أيضاً أن ضعف العلاقة بين المدرس والتلميذ يؤثر على ظهور سلوك العنف لدى التلاميذ, وأكد غالبية التلاميذ في المجموعة الأولى الذين مارسوا سلوك العنف, والمجموعة الثانية الذين لم يمارسوا سلوك العنف أن لبعض وسائل الإعلام دوراً في اكتساب التلاميذ لسلوك العنف. This study aims to identify the social and cultural factors that cause violent behavior among school students, the study population included students at the basic education level Episode II (seventh, eighth and ninth grade at secondary level) in Lattakia State schools in Syrian Arab Republic. The study reveals a correlation between the methods of punishment used by parents with students and their acquisition of violent behavior, and also reveals a relationship between social deprivation in the family and the emergence of violent behavior among students. The study results show that the weakness of the relationship between teacher and pupil affects the emergence of violent behavior among students, and also show that the majority of students in the first group who had violent behavior and the second group who did not exercise their violent behavior, assert the existence of the media role in the acquisition of pupils for violent behavior.